Pediatric bone tumors in Germany from 1987 to 2011: incidence rates, time trends and survival. (2nd October 2016) - Kaatsch, Peter; Strothotte, Jill; Becker, Cornelia; Bielack, Stefan; Dirksen, Uta; Blettner, Maria
Abstract: Background: Malignant bone tumors are a rare group of childhood cancer. Materials and methods: This study describes incidence rates, survival probabilities, and time trends for 1831 children below 15 years of age with a bone tumor registered at the population-based German Childhood Cancer Registry between 1987 and 2011. Results: Overall age-standardized annual incidence rate (ASR) was 5.5 per million. Osteosarcomas (ASR 2.8) and Ewing tumors (ASR 2.6) were the most frequent diagnostic groups. The incidence of bone tumors overall tended to increase slightly over time by 0.7% each year on average. Thirty-nine of the bone tumor cases reported were subsequent primaries and not included into the survival analysis. Survival probabilities remained largely constant. Discussion: Possibly survival was largely constant because chemotherapy has not changed much over time. Overall, the results are similar to other results reported from Europe.